THE EFFECTS OF SOCIAL ASSISTANCE PROGRAMS ON STUNTING PREVALENCE RATES IN INDONESIA - Munawaroh, Siti; Fajri, Moh Najikhul; Ajija, Shochrul Rohmatul (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2024)
Background: Social assistance, such as Non-Cash Food Assistance (BPNT) and the Family Hope Program (PKH), is among the instruments used to eradicate stunting in the short and long term. Therefore, it is important to ensure that individuals effectively use it. Aims: This study aimed to review the effect of social assistance on stunting prevalence rates in Indonesia. Methods: This research employs a quantitative approach, utilizing numerical measurements and statistical analysis. The data is secondary and sourced from the Central Bureau of Statistics and the Ministry of Finance. The specific method applied is the generalized method of moments (GMM) dynamic panel regression. The research sample encompasses panel data from 34 provinces from 2015 to 2021. This study utilizes the indicator of very short height for children less than five years of age as a proxy for stunting. Furthermore, low height in children is adopted as a measure of stunting. Furthermore, this study adopted a measure of low height in children to indicate stunting. Results: The results showed that social assistance negatively affected stunting, supported by various other indicators such as the proportion of proper sanitation, the average length of schooling, protein consumption, and drinking water sources. Meanwhile, excessive calorie consumption increases stunting in a certain period. Conclusion: In this condition, government social assistance was urgently needed since access to the lowest decile households increased stunting rates. The practical implications for policy derived from these findings involve optimizing the efficiency of social assistance initiatives, emphasizing the significance of addressing environmental factors in programs aimed at preventing stunting, integrating health and nutrition initiatives, and implementing educational campaigns within communities to raise awareness about calorie consumption. Keywords: child health, social assistance, stunting, toddlers